Sonographic appearances of the kidneys and correlation with CD4 count and viral load in adult HIV/AIDS patients in a rural-based infectious disease hospital in sub-saharan Africa - Ehi-Imuse AJ; Adeyekun AA; Irabor PFI; Azubike CO; Izevbekhai SO (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2023)
Background: The management of HIV infection is often challenging as it can affect every organ in the body including the kidneys. Determination of the Resistivity Indices (RI) of the intra-renal arteries is an emerging non-invasive tool that could predict renal disease.  Aims & objectives: To determine the renal volume, parenchymal pattern, as well as the RI of the intra-renal arteries by Doppler ultrasonography in adult HIV/AIDS patients and correlate findings with CD4 count, viral load and serum creatinine. Materials & methods: This is a comparative cross-sectional descriptive study that involved sonographic assessment of the renal dimensions, parenchymal echogenicity, and Doppler velocimetry of the segmental intra-renal arteries in 100 apparently healthy confirmed HIV-seronegative control subjects and an equal number of confirmed HIV-seropositive adult patients at Retroviral (RV) clinic of our hospital. A Doppler ultrasound machine with a 3.5MHz Curvilinear probe was used.  Data analysis: Data obtained was analyzed and presented as means which were compared using Student's t - test, and p values < 0.05 at 95% intervals were considered significant. Pearson's correlation coefficient was used to assess correlation. Results: The renal volumes were larger in the HIV/AIDS subjects (right: 125.94 ± 34.02 cm3 and left: 138.99 ± 33.29cm3) than in controls (p = < 0.01) with the left also larger than the right in both HIV/AIDS and control subjects (p = < 0.01, < 0.01) respectively.  There were significantly more individuals with abnormal renal echogenicity in the HIV/AIDS subjects than in the controls. The RI was significantly greater in the HIV/AIDS than in control subjects.  Both renal volumes showed a weak negative correlation with CD4, viral load, and serum creatinine which was not statistically significant.  There was a statistically significant weak negative correlation between renal echogenicity and CD4 but a positive correlation with viral load and serum creatinine.  RI showed weak negative correlations with serum creatinine and weak positive correlations with CD4 count.  Conclusion: There is a significant difference in renal volume, echogenicity, and RI in HIV/AIDS patients compared to the controls. Renal echogenicity is a better predictor of serum creatinine levels than renal volume and RI. Thus, renal volume and RI do not provide sufficient correlation to be used as a means of monitoring HIV/AIDS patients with renal impairment.